RESOLUSI KONFLIK OLEH DINAS TENAGA KERJA KABUPATEN INDRAGIRI HULU PADA KONFLIK KARYAWAN DAN PT. SINAR REKSA KENCANA - Riska Indriyana Putri; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Disputes in industrial relations are common in the world. Industrial relations disputes according to Law no. 2 of 2004 concerning the Settlement of Industrial Relations Disputes (UU PPHI) is a difference of opinion that results in conflict between employers or a combination of employers and workers/labor or trade unions/labor unions. One of them is the conflict between PT. Sinar Reksa Kencana and its employees, started with the mass Termination of Employment carried out by PT. Sinar Reksa Kencana due to an acquisition by the Mentari Group. This study aims to determine the inhibiting factors of conflict resolution and how the role of the government in carrying out conflict resolution at PT. Sinar Mutual Kencana in Indragiri Hulu Regency. This research is a descriptive qualitative research where data collection uses observation, interviews, and documentation techniques. This study uses the resolution theory put forward by Fisher in (Tisa, 2017), namely Negotiation, Mediation, and Arbitration. One of the obstacles when resolving industrial relations disputes is the lack of knowledge of both parties and the absence of agreement or disagreement, causing disputes and lack of understanding of different labor laws and regulations, and third parties finally provide assistance to both parties. Keyword : Resolutions , Conflict, Industrial Conflict